Directional pore channel interconnected dual-network xerogel as well as preparation method and application thereof

Through the polyacrylamide/lithium alginate-molybdenum sulfide dual network x-gel interconnected with directional pores, the dehydration and adsorption-desorption rate problems of hygroscopic agents are solved, efficient hygroscopic and low energy consumption water production under different humidity environments, and the circulation stability and photothermal conversion efficiency of the material are improved.

CN120399314APending Publication Date: 2025-08-01GUIZHOU UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510623852.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-15
Publication Date
2025-08-01

AI Technical Summary

Technical Problem

The existing hygroscopic agents are prone to dehydration after hygroscopy, slow adsorption-desorption rate, poor circulation stability, high regeneration energy consumption, and insufficient long-term circulation stability of photothermal materials in the actual environment, making it difficult to achieve low energy consumption hygroscopic and water production synergistic effects.

Method used

A polyacrylamide/lithium alginate-molybdenum sulfide dual network x-gel with directional channel interconnection was used to construct a three-dimensional interpenetrating network through the ice template method, combining LiCl as a hygroscopic component and MoS2 as a photothermal conversion material to form a directional channel structure to achieve rapid adsorption and efficient regeneration of hygroscopic agents.

Benefits of technology

It exhibits excellent moisture absorption performance and stable desorption ability in high, medium and low humidity environments, with an average daily water production of 2.99L/(m2·d), and achieves low energy consumption dehumidification and water production synergistic efficiency under solar power drive.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120399314A_ABST
    Figure CN120399314A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of composite material preparation, and discloses oriented pore channel interconnected dual-network xerogel and a preparation method and application thereof.The method comprises the steps that firstly, acrylamide monomers, molybdenum sulfide nanosheets and sodium alginate powder are mixed and then dispersed in 35 mL of ultrapure water, and a homogeneous transparent precursor solution is formed; injecting the precursor solution into a mold to prepare molded hydrogel, loading the molded hydrogel into a brass mold, and performing directional freezing treatment to prepare PSM; the preparation method comprises the following steps: dipping PSM in a lithium chloride solution, carrying out directional freezing treatment, and then carrying out freeze-drying treatment to prepare the dual-network xerogel PSML. The dual-network xerogel PSML provided by the invention not only solves the problems of easy deliquescence, slow adsorption-desorption rate, poor cycle stability and high regeneration energy consumption of a moisture absorbent after moisture absorption, but also has excellent moisture absorption capability, photothermal conversion efficiency, water desorption performance and cycle stability; and high-efficiency low-energy-consumption indoor dehumidification and solar-driven atmosphere water collection can be realized synchronously.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a preparation method of a double-network dry gel with oriented pore channels interconnected, specifically to a composite material for solar-driven air moisture absorption and water production, belonging to the technical field of composite material preparation. Background Art

[0002] The shortage of water resources has become a global challenge. Although seawater desalination technology is the main way to alleviate the problem of water resource shortage, the carbon footprint and cost of this technology are relatively high and it is restricted by the uneven distribution of seawater. The atmosphere is rich in 1.3 trillion tons of gaseous water, which is not restricted by time and space and is an available fresh water resource. Capturing water in the air based on adsorption technology can not only obtain fresh water, but also achieve low-energy dehumidification, with dual benefits.

[0003] The air moisture absorption and water production technology is a new integrated technology that is safe, low-carbon, and green, based on adsorption technology for atmospheric moisture absorption and solar-driven photothermal water production. It can not only achieve low-energy indoor dehumidification, but also produce water through the solar-induced photothermal conversion effect, aiming to improve the indoor air quality and prepare low-cost, environmentally friendly clean water at the same time. Hygroscopic salts, as low-cost and easily accessible adsorbents in this technology, have good moisture absorption ability. However, salts are prone to deliquescence after absorbing water, which severely restricts their reuse performance and significantly reduces the cycle stability. In addition, in order to achieve low-energy water production, how to couple it with photothermal materials to synergistically achieve low-energy water production and adsorbent regeneration is an important technical challenge; the long-term cycle stability of photothermal hygroscopic composite materials in the actual environment has also attracted much attention. Summary of the Invention

[0004] Aiming at the above technical problems, the present invention provides an oriented pore channels interconnected double-network dry gel, its preparation method and application. This dry gel not only solves the problems of easy deliquescence of the hygroscopic agent after moisture absorption, slow adsorption-desorption rate, poor cycle stability, and high regeneration energy consumption, but also has excellent moisture absorption ability, photothermal conversion efficiency, water desorption performance and cycle stability.

[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0006] The first object of the present invention is to provide a preparation method of an oriented pore channels interconnected double-network dry gel, comprising the following steps:

[0007] Step 1: First, mix acrylamide monomer, molybdenum disulfide nanosheets and sodium alginate powder in a mass ratio of 3:0.1-0.3:0.15-1, then disperse them in 35 mL of ultrapure water. After ultrasonic treatment, add a crosslinking agent and an initiator, and stir evenly to form a homogeneous transparent precursor solution;

[0008] Step 2: Inject the precursor solution into a mold, and conduct thermal-initiated polymerization in a water bath environment at 50 - 70 °C for 1 - 3 h to form a primary cross-linked network and obtain a shaped hydrogel. Then load the shaped hydrogel into a brass mold, place it in a liquid nitrogen environment for directional freezing treatment, and then transfer it to a freeze dryer to maintain for 48 h to remove the ice crystal template, finally obtaining a polyacrylamide / sodium alginate-molybdenum disulfide double-network dry gel (PSM) with highly oriented pores;

[0009] Step 3: Dissolve lithium chloride in ultrapure water to obtain a lithium chloride solution. Then immerse the PSM in the lithium chloride solution with a concentration of 0.009 - 0.108 g / mL for 24 hours. After directional freezing treatment, conduct freeze-drying treatment for another 48 hours to obtain a polyacrylamide / lithium alginate-molybdenum disulfide double-network dry gel (PSML).

[0010] In the above method, the molybdenum disulfide nanosheets are prepared by dissolving sodium molybdate and L-cysteine in a molar ratio of 2:4 in 30 mL of ultrapure water, then placing them in a hydrothermal autoclave for hydrothermal reaction. The hydrothermal reaction temperature is 200 °C, the hydrothermal time is 12 h, and then drying is carried out at 80 °C.

[0011] In the above method, the cross-linking agent is N,N'-methylenebisacrylamide, and its content is 0.05 - 0.20% of the monomer mass.

[0012] In the above method, the initiator is ammonium persulfate, and its content is 5.0% of the monomer mass.

[0013] The second object of the present invention is to provide the polyacrylamide / lithium alginate-molybdenum disulfide double-network dry gel (PSML) obtained by the above preparation method.

[0014] The third object of the present invention is to provide the application of the above polyacrylamide / lithium alginate-molybdenum disulfide double-network dry gel (PSML) in solar-driven air hygroscopic water production.

[0015] Compared with the prior art, the advantages of the present invention are as follows:

[0016] 1. The present invention adopts an ice-templating method for directional freezing-drying-impregnation process, and constructs a polyacrylamide / lithium alginate-molybdenum disulfide (PSML) interpenetrating double-network dry gel composite material with a directional pore structure. This composite material uses polyacrylamide (PAM) and lithium alginate (SA) to form an interpenetrating double-network matrix, LiCl as an efficient moisture-absorbing component, and molybdenum disulfide nanosheets (MoS2) as a photothermal conversion material. Benefiting from the directional pore channels constructed by the ice crystal templating method and the three-dimensional interpenetrating double-network synergistic structure, this composite material exhibits excellent moisture absorption performances of 3.68 g / g, 1.38 g / g, and 0.73 g / g in high (90% RH), medium (60% RH), and low (30% RH) humidity environments respectively, and the corresponding adsorption equilibrium times are shortened to 4 - 5, 2 - 3, and 1 - 2 hours. In addition, this composite material has a stable desorption ability under different light intensity conditions and can adapt to the fluctuating characteristics of solar irradiation in the actual environment.

[0017] 2. The excellent performance of the present invention stems from three key designs: ① The three-dimensional interpenetrating network significantly increases the specific surface area and enhances the water molecule capture efficiency through capillary action; ② A synergistic water storage mechanism based on the interaction between PAM amide bonds, SA hydroxyl groups, and LiCl ions forms a dual water storage site containing a hydrogen bond network (PAM-SA-H2O) and ion hydration (Li + -H2O); ③ The directionally arranged micron-scale pore channels reduce the mass transfer resistance and achieve rapid water vapor transport. The PSML sample not only has excellent moisture absorption cycle stability, but also the daily average water production driven by solar energy measured through outdoor experiments reaches 2.99 L / (m 2 ·d). This structure-function integrated design breaks through the technical bottlenecks of traditional moisture absorption materials, such as poor humidity adaptability and high regeneration energy consumption.

[0018] 3. Based on the new "air-solar energy-water" ternary fusion model, the present invention designs a composite material with integrated low-energy air moisture absorption and solar photothermal water production. Driven by clean energy, this composite material realizes the synergistic effect of carbon reduction, dehumidification, and water production. Therefore, the present invention provides a feasible solution for alleviating the shortage of fresh water resources, promoting the improvement of indoor air quality, and reducing carbon emissions. Description of the Drawings

[0019] Figure 1 (a) is the SEM image (SEM is the abbreviation of Scanning electron microscope, i.e., scanning electron microscopy) of the surface of the polyacrylamide / sodium alginate-molybdenum disulfide double-network dry gel (PSM) in the embodiment of the present invention;

[0020] Figure 1 (b) is the SEM image of the longitudinal section of PSM in the embodiment of the present invention;

[0021] Figure 1 (c) is the SEM image of the surface of polyacrylamide / lithium alginate-molybdenum disulfide double network dry gel (PSML) and its magnification in the embodiment of the present invention;

[0022] Figure 1 (d) is the SEM image of the longitudinal section of PSML in the embodiment of the present invention;

[0023] Figure 1 (e) is the SEM image of molybdenum disulfide nanosheets (MoS₂) in the embodiment of the present invention;

[0024] Figure 1 (f) is the SEM image of MoS₂ in the PSML sample in the embodiment of the present invention;

[0025] Figure 1 (g) is the energy dispersive spectroscopy (EDS) image of PSML in the embodiment of the present invention;

[0026] Figure 2 is the FTIR image of acrylamide (AM), sodium alginate (SA), polyacrylamide / sodium alginate (PS), polyacrylamide / sodium alginate-molybdenum disulfide (PSM), polyacrylamide / lithium alginate (PSL), and polyacrylamide / lithium alginate-molybdenum disulfide (PSML) in the embodiment of the present invention (FTIR is the abbreviation of Fourier Transform Infrared Spectroscopy);

[0027] Figure 3 is the water contact angle image of PS, PSM, and PSML in the embodiment of the present invention;

[0028] Figure 4 (a) is the moisture absorption performance of PSML with different SA contents at 25 °C and 80% RH in the embodiment of the present invention;

[0029] Figure 4 (b) is the schematic diagram of the moisture absorption performance of PSML with different MBA contents at 25 °C and 80% RH in the embodiment of the present invention;

[0030] Figure 4 (c) is the schematic diagram of the moisture absorption performance of PSML with different LiCl contents at 25 °C and 90% RH in the embodiment of the present invention;

[0031] Figure 4 (d) is the schematic diagram of the moisture absorption performance of PSML with different LiCl contents at 25 °C and 80% RH in the embodiment of the present invention;

[0032] Figure 4(e) is a schematic diagram of the moisture absorption performance of PSML with different LiCl contents at 25 °C and 60% RH in the embodiments of the present invention;

[0033] Figure 4 (f) is a schematic diagram of the moisture absorption performance of PSML with different LiCl contents at 25 °C and 30% RH in the embodiments of the present invention;

[0034] Figure 5 (a) is a schematic diagram comparing the moisture absorption of LiCl, the disordered pore structure (PSML-random) prepared by ordinary freeze-drying method, and the PSML sample at 25 °C and 90% RH in the embodiments of the present invention;

[0035] Figure 5 (b) is a schematic diagram comparing the moisture absorption rates of LiCl, the disordered pore structure (PSML-random) prepared by ordinary freeze-drying method, and the PSML sample at 25 °C and 90% RH in the embodiments of the present invention;

[0036] Figure 6 is a schematic diagram of the moisture absorption cycle stability test of PSML at 25 °C and 90% RH in the embodiments of the present invention;

[0037] Figure 7 (a) is a schematic diagram of the solar reflectance of PSM and PSML in the embodiments of the present invention;

[0038] Figure 7 (b) is a UV-VIS-NIR diagram of PSM and PSML in the embodiments of the present invention (UV-VIS-NIR is the abbreviation of Ultraviolet-Visible-Near infra-red, that is, ultraviolet-visible-near infrared spectrum);

[0039] Figure 7 (c) is a schematic diagram of the water desorption amount of PSL with different MoS2 contents under simulated 1 sun irradiation in the embodiments of the present invention;

[0040] Figure 7 (d) is a schematic diagram of the water desorption amount of PSML under simulated 0.6, 0.8, and 1.0 sun irradiations in the embodiments of the present invention;

[0041] Figure 8 (a) is a full flow chart of the outdoor experiment of solar-driven moisture absorption and water production in the embodiments of the present invention;

[0042] Figure 8 (b) is a schematic diagram of the temperature and humidity curves during the moisture absorption process of the outdoor experiment of solar-driven moisture absorption and water production in the embodiments of the present invention;

[0043] Figure 8(c) is a schematic diagram of the temperature and humidity curves during the water desorption process of the outdoor experiment of solar-driven hygroscopic water production in the embodiments of the present invention;

[0044] Figure 8 (d) is a schematic diagram of the moisture absorption amount, water release amount and water collection amount in the outdoor experiment cycle test of solar-driven hygroscopic water production in the embodiments of the present invention;

[0045] Figure 8 (e) is a schematic diagram of the water quality analysis of the collected water in the outdoor experiment of solar-driven hygroscopic water production in the embodiments of the present invention. Detailed implementation manners

[0046] In order to make the objectives, technical solutions and advantages of the present invention clearer, the present invention will be further described in detail below with reference to the accompanying drawings and embodiments.

[0047] The present invention provides a preparation method of a dual-network dry gel with oriented pore channels, including the following steps:

[0048] Step 1: First, mix acrylamide monomers, molybdenum disulfide nanosheets and sodium alginate powder in a mass ratio of 3:0.1-0.3:0.15-1, then disperse them in 35 mL of ultrapure water. After ultrasonic treatment, add a crosslinking agent and an initiator, and stir evenly to form a homogeneous transparent precursor solution;

[0049] Step 2: Inject the precursor solution into a mold, and perform thermal-initiated polymerization in a water bath environment at 50-70 °C for 1-3 h to form a primary cross-linked network to obtain a shaped hydrogel. Then load the shaped hydrogel into a brass mold, place it in a liquid nitrogen environment for directional freezing treatment, and then transfer it to a freeze dryer to maintain for 48 h to remove the ice crystal template, and finally obtain a polyacrylamide / sodium alginate-molybdenum disulfide dual-network dry gel (PSM) with highly oriented pores;

[0050] Step 3: Dissolve lithium chloride in ultrapure water to obtain a lithium chloride solution. Then immerse the PSM in a lithium chloride solution with a concentration of 0.009-0.108 g / mL for 24 hours. After directional freezing treatment, perform freeze-drying treatment for another 48 hours to obtain a polyacrylamide / lithium alginate-molybdenum disulfide dual-network dry gel (PSML).

[0051] In the above method, the molybdenum disulfide nanosheets are prepared by dissolving sodium molybdate and L-cysteine in a molar ratio of 2:4 in 30 mL of ultrapure water, then placing them in a hydrothermal kettle for hydrothermal reaction. The hydrothermal reaction temperature is 200 °C, the hydrothermal time is 12 h, and then drying is carried out at 80 °C.

[0052] In the above method, the crosslinking agent is N,N'-methylenebisacrylamide, and its content is 0.05-0.20% of the monomer mass.

[0053] In the above method, the initiator is ammonium persulfate, and its content is 5.0% by weight of the monomer.

[0054] After analysis and experiments, it can be seen that the directional pore interconnected porous polyacrylamide / lithium alginate-molybdenum sulfide double network dry gel (PSML) obtained by the above preparation method not only solves the problems of easy deliquesce of the desiccant after moisture absorption, slow adsorption-desorption rate, poor cycle stability, and high regeneration energy consumption, but also has excellent moisture absorption capacity, photothermal conversion efficiency, water desorption performance and cycle stability.

[0055] The polyacrylamide / lithium alginate-molybdenum sulfide double network xerogel (PSML) prepared by the above method was characterized, and it was found that it has the following properties:

[0056] (1) According to SEM observation, the PSM formed by copolymerization of PAM and SA has a three-dimensional porous network structure with thin walls (e.g. Figure 1 As shown in a), due to the directional freezing process of the ice template method, the ice crystals induced directional growth. After freeze-drying, the ice crystals sublimated and formed directional channels in the hydrogel. Therefore, the longitudinal cross-section formed by the PSM showed a highly directional and uniform pore structure (as shown in Figure 1 b), showing thin-walled honeycomb features, with pore size distribution concentrated between 20 and 30 μm. After being immersed in LiCl solution and cross-linked, the surface of the PSML sample changed, showing a filamentous network structure, and the pore wall became relatively rough and thick (as shown in Fig. Figure 1 c), which is beneficial to enhance the mechanical stability of the sample; similarly, the longitudinal section of PSML also shows the same pore orientation as PSM, and these pores are interconnected, but the pore size is slightly smaller due to the cross-linking effect between SA and Li+ (as shown in Figure 1 d). In addition, it is worth noting that the modified MoS2 presents a hydrangea shape with flakes stacked (as shown in Figure 1 e), and accordingly, MoS2 attached to the pore wall was also observed in PSML (as shown in Figure 1 f). According to the element surface scan (such as Figure 1 f), the skeleton composed of three elements of C, N, and O can be seen intuitively, indicating that PAM and SA form a porous skeleton of the composite sample. In addition, Cl and Mo elements are evenly distributed on the skeleton, indicating that LiCl and MoS2 are successfully loaded on the sample, effectively solving the agglomeration problem of hygroscopic salt in the salt-based composite adsorbent.

[0057] (2) FT-IR was used to study the interaction mechanism between PAM, LiCl, SA and MoS2 and the changes in chemical bonds when various monomers were introduced. Figure 2 As shown, the characteristic peak of the original AM monomer is 3350cm -1 and 3189cm-1 The doublet at -1 corresponds to the symmetric and antisymmetric stretching vibrations of the secondary amino group (N-H), and the strong absorption peak at 1672 cm -1 corresponds to the stretching vibration of the carbonyl group (C=O), while the vibrations at 1612 cm -1 and 1428 cm -1 are the vibration modes of the C=C double bond and the C-N single bond, respectively. It should be noted that the doublets at 1604 cm -1 and 1416 cm -1 in the SA component correspond to the asymmetric and symmetric stretching vibrations of the carboxylate group (-COO-), respectively, and the weak peak at 2927 cm -1 originates from the vibration of the methylene group (C-H). After the polymerization reaction, the complete disappearance of the C=C characteristic peak at 1612 cm -1 in samples such as PS and PSM indicates the successful conversion of the AM monomer into the PAM network structure. The N-H peak at 3189 cm -1 of the AM monomer broadens at PS and PSM, which is attributed to the N···H stretching vibration in the H-N···HO bond formed by the amino group in the PAM segment and the hydroxyl group of the SA molecule, indicating the interaction between the lone pair electrons on -N in PAM and the -H atom of SA, proving that PAM and SA copolymerize together. The synchronous appearance of the C=O peak at 1672 cm -1 in samples of PS, PSM, PSL, and PSML redshifts to 1653 cm -1 and the absorption intensity decreases, further verifying the intermolecular interaction between PAM and SA through hydrogen bonding. After introducing LiCl, significant changes occur in the infrared spectra of the PSL and PSML samples. The asymmetric vibration peak of -COO- in the SA component shifts from 1604 cm -1 to 1629 cm -1 in the PSL and PSML samples, and the symmetric vibration peak shifts from 1416 cm -1 to 1421 cm -1 in the PSL sample and from 1416 cm -1 to 1425 cm

[0058] in the PSML sample, and the absorption intensity decreases simultaneously. This blue shift phenomenon can be attributed to the coordination of the carboxylate group in the G unit of sodium alginate with Li+. The amide bond on PAM and the hydroxyl group on SA are both beneficial to improving the water-binding ability. In addition, LiCl is connected to the SA molecular chain through ionic interaction, and its strong hydration effect strengthens the binding of SA to surrounding water molecules at the same time. Therefore, through the hydrogen bonds between PAM and water molecules, SA and water molecules, and PAM and SA, the ionic interaction and hydration of LiCl form a three-hydrogen bond system that tightly combines PAM, SA, and LiCl, while achieving excellent water-binding ability.(3) To evaluate the hydrophilicity and hydrophobicity of the prepared sample surfaces, water contact angle tests were carried out on PS, PSM, and PSML series samples (as Figure 3 shown). The experimental results showed that within 200 ms of the water droplet contacting the surface, all three samples exhibited hydrophilicity, with contact angles less than 90°. Among them, the contact angle of PS was 39.6°, which was mainly attributed to the synergistic effect of hydrophilic functional groups such as the amino groups of the polyacrylamide chain segments in PS and the carboxyl groups of sodium alginate molecules. It should be noted that the water contact angle of the PSM sample slightly increased to 46.8° after adding the photothermal material MoS2, but still remained significantly hydrophilic, indicating that the addition of the photothermal component MoS2 did not significantly change the intrinsic hydrophilicity of the material. On this basis, after cross-linking with the hygroscopic salt LiCl, the sample contact angle decreased to 31.3° again, indicating that the PSML sample was more hydrophilic, confirming that the loading of hydrophilic salts could effectively enhance the hydrophilic characteristics of the material surface and interface, which provided a theoretical support for the moisture absorption performance of the subsequent samples under a wide range of humidities.

[0059] (4) To clarify the structure-activity relationship of the double-network structure components and further explore the influence law of the cross-linking agent content on the moisture absorption of the material. In a constant humidity environment of 25 °C and 80% RH, a series of samples were prepared by setting the concentration gradient of the cross-linking agent MBA (0.05% - 0.50%). The experimental data (as Figure 4 shown in Fig. a) showed that when the MBA content increased from 0.05% to 0.20%, the moisture absorption capacity of the sample gradually increased from 1.47 g / g to 1.57 g / g, which was mainly attributed to the three-dimensional network formed by moderate cross-linking enhancing the water molecule adsorption sites. However, when the MBA concentration reached 0.50%, excessive cross-linking led to the densification of the network structure, and the moisture absorption amount decreased to 1.50 g / g instead, indicating that 0.20% was the optimal cross-linking agent addition amount. At the same time, the content of the second network component SA had a significant regulatory effect on the moisture absorption performance (as Figure 4 shown in Fig. b). Since the single-network PML sample lacked the support of the interpenetrating network, the moisture absorption amount was only 0.53 g / g. After introducing SA to construct a double-network system, the secondary network formed by its molecular chains effectively penetrated the internal pores, increasing the diffusion rate of water molecules. When the mass ratio of AM / SA was optimized to 5:1, the moisture absorption amount of the PSML sample increased to 1.59 g / g, nearly three times higher than that of the single-network system. This phenomenon confirmed that the double-network synergistic effect could significantly improve the mass transfer kinetics of the material. Using the optimal concentrations of the above two components to construct a system to study the influence of different hygroscopic salt loadings on the moisture absorption of the system, with the increase of the impregnation LiCl concentration (0 - 0.9 L), the moisture absorption amount of the sample increased significantly, reaching 3.68 g / g at 90% relative humidity (as Figure 4As shown in c), the actual content of LiCl in the composite sample is 64.1% at this time, achieving a high loading of the hygroscopic salt. However, when the LiCl concentration is too high (1.08 L), the LiCl in the composite adsorbent will block the internal pores of the double network, resulting in a decrease in the moisture absorption capacity. Therefore, it is determined that 0.9 L of LiCl is the optimal concentration for preparing the sample. Then, the moisture absorption characteristics of the modified sample in a wide range of humidity environments are further studied. The test data show that the interconnected porous double network structure exhibits excellent humidity adaptation ability. Specifically, under the conditions of high relative humidity of 90% and 80% (as shown in Figure 4 d), the moisture absorption amounts of PSML reach 3.68 g / g and 2.24 g / g within 4 to 5 hours respectively, indicating its rapid response characteristics in a high humidity environment. This rapid adsorption kinetic feature benefits from the through-mass transfer channels formed by the interpenetrating network. In a medium humidity environment (60% RH), the adsorption equilibrium time is shortened to 2 to 3 hours, and the corresponding moisture absorption amount is 1.38 g / g ( Figure 4 e). It is worth noting that even under the low humidity condition of 30% RH, PSML still maintains an effective moisture absorption capacity of 0.73 g / g (as shown in Figure 4 f), achieving efficient moisture absorption of the moisture-absorbing composite material at low humidity. The collaborative design of the interconnected porous network and the oriented pore channels significantly optimizes the water molecule diffusion path, enabling PSML to have a wide range of humidity adaptation ability, providing key performance support for its application under actual working conditions.

[0060] (5) To clarify the structural advantages of the double network, a series of comparative experiments are designed to verify its moisture absorption kinetic characteristics. Two control groups are set up in the experiment, namely pure LiCl powder and the PSML-random sample with a disordered pore structure prepared by the ordinary freeze-drying method. Through Figure 5 The kinetic test data in a show that the moisture absorption amounts of the two groups of samples with the double network structure are higher than that of LiCl in the first 4 to 5 hours of moisture absorption, and the initial moisture absorption rate of the PSML sample reaches 2.39 g / g / h, which is 3.62 times that of LiCl (0.66 g / g / h) and 1.77 times that of PSML-random (1.35 g / g / h) respectively ( Figure 5 a). This performance improvement is attributed to the significant increase in the effective contact area with water molecules by the three-dimensional interpenetrating porous structure, and the oriented pore channels constructed by the ice crystal template method can reduce the mass transfer resistance. The control experiment also reveals the difference in material stability. Pure LiCl cannot be reused because it forms a salt solution after moisture absorption and deliquescence, while PSML still maintains a high adsorption capacity after five cycles (as shown in Figure 6As shown, its structural stability advantage is demonstrated. Therefore, the oriented pore channels for the rapid mass transfer of water molecules and the dual-network cooperative water storage mechanism are the key factors for improving the moisture absorption efficiency. In summary, through comparative experiments, the present invention reveals the influence of the microstructure on the mass transfer efficiency and clarifies the water adsorption mechanism of different material systems. LiCl directly captures gaseous water molecules through physicochemical adsorption to form a liquid salt solution, while the PSML-random disordered structure has tortuous pore channels, forcing water molecules to experience a tortuous diffusion path to reach the internal adsorption sites. In contrast, the oriented pore channel structure of the dual-network hydrogel exhibits significant advantages. Its oriented pore system not only reduces the mass transfer resistance but also enables the multi-directional and rapid migration of water molecules through a three-dimensional interconnected porous network.

[0061] (6) Optimizing the desorption process is the core link to improve the technical performance of the moisture absorption and water production technology, and its kinetic characteristics directly determine the cycle life and water production efficiency of the material. To achieve a low-energy-consuming and sustainable desorption process, this study optimized the structure of the photothermal conversion system. Through precursor screening and improvement of the synthesis route, molybdenum disulfide (MoS2) nanomaterials with a layered stacked structure were prepared by the hydrothermal method. After integrating the optimized MoS2 into the composite system, the system achieved efficient water molecule desorption under solar irradiation, providing a reliable technical solution for the continuous water production process driven by solar energy. This study evaluated the light absorption characteristics of the composite samples through spectral reflectance tests (such as Figure 7 as shown in Fig. a). The experimental data showed that after moisture absorption, the wide-spectrum reflection behaviors of the PSL (the sample appears white) and PSML (the sample appears black) samples without the introduction of photothermal components showed significant differences. Compared with PSL, the reflectivity of PSML decreased significantly. Based on the absorption rate calculation, in the ultraviolet-visible-near-infrared spectral range, the light capture efficiency of PSML was as high as 98.8%, much higher than 32.8% of PSL (as shown in Figure 7 Fig. b). This value indicates that the optimized PSML system has excellent broadband light absorption ability, providing an effective energy conversion basis for photothermal-driven water desorption. Further study the regulation mechanism of the photothermal component on the water desorption kinetics. The experimental data (such as Figure 7As shown in Figure c, after 8 hours of moisture absorption in an environment of 25 °C and 90% RH, the samples all reached an equilibrium adsorption capacity of approximately 3.5 g / g, confirming that the introduction of MoS2 did not significantly change the intrinsic moisture absorption capacity of the material. However, under 1 sun light illumination, the desorption kinetics showed significant differences: the PSL system without the addition of a photothermal component exhibited obvious desorption hysteresis, releasing only 1.04 g / g of water in 1.5 hours, and the residual water content accounted for 70%. After introducing 0.1 g of MoS2, the desorption amount increased to 2.20 g / g, and the desorption efficiency increased by approximately 2.1 times. When the MoS2 addition amount increased to 0.3 g, the desorption amount reached 2.84 g / g, corresponding to a desorption efficiency increase to 82%. It should be noted that when the MoS2 addition amount exceeded 0.3 g, gelation failed due to hindered cross-linking of the precursor, indicating that this value was the optimal doping amount. To further verify the environmental adaptability of the system, the desorption behavior of PSL-0.3M under different irradiation intensities was tested (as shown in Figure d). The experimental data showed that when the light intensity increased from 0.6 sun to 1.0 sun, the desorption amount increased from 2.12 g / g to 2.86 g / g, and the residual water content decreased to 0.64 g / g. It was confirmed that the system had a stable desorption ability under a wide range of light intensity conditions and could adapt to the fluctuating characteristics of solar irradiation in the actual environment. The present invention realizes efficient water production through a photothermal - water evaporation synergy mechanism: the hydrangea-like MoS2 converts light energy into heat energy to heat the system, the directional pores transport water to the surface interface through capillary action, and the interconnected porous network is conducive to reducing the steam diffusion resistance, and finally fresh water is condensed. This structure - function integrated design provides new possibilities for solar-driven moisture absorption and water production. Figure 7 As shown in Figure d

[0062] (7) To further evaluate the actual application performance of PSML, the present invention carried out an enlarged outdoor experiment aiming to deeply explore its effectiveness in water vapor adsorption and solar-driven water production. As shown in Figure a Figure 8 , 23 PSMLs were placed in a self-made water collection device and subjected to moisture absorption operation overnight (for 12 h) in the outdoor environment. During this period, environmental parameters were monitored and recorded in real time using a temperature and humidity recorder (as shown in Figure b and Figure Figure 8 Figure Figure 8(as shown in c) (temperature is 10 - 20 °C, relative humidity is 70 - 90% RH). The next day, the condensation cover tightly covers the water collection device, and by using the photothermal conversion effect of the composite component with natural sunlight, the sample is prompted to release the adsorbed water. During the 1.5-hour natural light illumination process, the solar radiation intensity is continuously measured, and its value fluctuates between 0.5 and 0.9 solar light intensities, while the average solar radiation intensity of the entire solar energy-driven water production process is stable at 0.8 solar light intensities. Experimental observations found that once the sunlight illumination starts, condensed water droplets quickly appear on the inner wall of the condensation cover within 10 minutes, indicating that the adsorbed water in the sample is gradually being released. After 60 minutes, the surface of the condensation cover of the experimental device is densely covered with small water droplets. After measurement, the amount of water released from the sample is 1.27 g / g. However, due to objective factors such as residual water on the inner wall of the device and heat dissipation, the finally actually collected amount of water is 1.04 g / g. Through calculation, the daily average water production of this device in the solar energy-driven mode can reach 2.99 L / (m 2 ·d). To further strongly verify the excellent cycle stability of the PSML material, we carried out 6 outdoor tests (as shown in Figure 8 d). For the collected water samples, the ion concentrations were measured, and the results showed (as shown in Figure 8 e) that the concentrations of K+, Ca 2 +, Na+, Mg 2 +, Cl-, F-, NO3- and SO4 2- as well as the TOC concentration are all far lower than the limit values set by the WHO for the safety standards of drinking water, proving that the quality of the collected water is safe and reliable and meets the quality requirements of drinking purified water.

[0063] Several specific embodiments of the preparation method disclosed in the present invention are listed below. The described embodiments are only a part of the embodiments of the present invention. All embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts belong to the scope protected by the present invention.

[0064] Example 1

[0065] Dissolve 2 mmol of sodium molybdate and 4 mmol of L-cysteine in 30 mL of ultrapure water, then place it in a hydrothermal reactor for hydrothermal reaction. The hydrothermal reaction temperature is 200 °C and the hydrothermal time is 12 h. Then dry it at 80 °C to obtain molybdenum sulfide nanosheets (MoS₂); Disperse 3.0 g of acrylamide monomer and 0.3 g of molybdenum sulfide nanosheets in 30 mL of ultrapure water, and ultrasonic treatment for 20 min to achieve uniform dispersion. Add the corresponding amount of SA powder according to the mass ratio of acrylamide (AM) to sodium alginate (SA) of 3:0.15, and then transfer it to a 60 °C constant temperature water bath and stir continuously for 1 h to ensure uniform dispersion of each component. After the mixed solution is cooled to room temperature, inject the crosslinking agent N,N'-methylenebisacrylamide (MBA) at 0.2% of the monomer mass in sequence, and magnetic stirring for 1 min to promote molecular pre-crosslinking. Continue to introduce the ammonium persulfate initiator (APS) at 5.0% of the monomer mass, stir briefly and then eliminate the residual bubbles by ultrasonic degassing treatment to obtain a homogeneous transparent precursor solution. Use a 1 mL syringe to quantitatively absorb this solution, and carry out thermal-initiated polymerization in a 60 °C water bath environment for 2 h to form a primary crosslinked network. Wash the product with ultrapure water multiple times to completely remove the residual monomers that did not participate in the reaction. Construct a directional pore structure by the ice template method, load the formed hydrogel into a brass mold, and place it in a liquid nitrogen environment for directional solidification treatment to make the ice crystals preferentially grow along the temperature gradient direction. Then transfer it to a freeze dryer and maintain it for 48 h to remove the ice crystal template, and finally obtain a polyacrylamide / lithium alginate-molybdenum disulfide double network dry gel (PSM) with highly oriented pores. Dissolve mass gradients (0.09, 0.18, 0.36, 0.54, 0.72, 0.90, 1.08 g) of LiCl in 10 mL of ultrapure water, then immerse the PSM in each concentration solution for 24 hours, after directional freezing treatment, and finally freeze-dry for 48 hours to obtain PSM-0.09L, PSM-0.18L, PSM-0.36L, PSM-0.54L, PSM-0.72L, PSM-0.90L, PSM-1.08L samples in sequence.

[0066] The directionally porous interconnected polyacrylamide / lithium alginate-molybdenum disulfide double network dry gel (PSML) with a lithium chloride addition amount of 0.9 L prepared in Example 1 of the present invention was characterized by SEM, FT-IR, water contact angle, and UV-VIS-NIR.

[0067] The directionally porous interconnected polyacrylamide / lithium alginate-molybdenum disulfide double network dry gel (PSML) prepared in Example 1 of the present invention was tested for indoor moisture absorption performance. The specific process is as follows: Place the PSML sample prepared in Example 1 in a constant temperature and humidity chamber, and absorb moisture at a temperature of 25 °C and a relative humidity of 80% RH. The moisture absorption amount is 1.19 g / g.

[0068] Example 2

[0069] Dissolve 2 mmol of sodium molybdate and 4 mmol of L-cysteine in 30 mL of ultrapure water, and then place it in a hydrothermal autoclave for hydrothermal reaction. The hydrothermal reaction temperature is 200 °C and the hydrothermal time is 12 h. Then dry it at 80 °C to obtain molybdenum disulfide (MoS₂). Disperse 3.0 g of acrylamide monomer and 0.3 g of molybdenum disulfide nanosheets in 30 mL of ultrapure water, and ultrasonically treat for 20 min to achieve uniform dispersion. Add the corresponding amount of SA powder according to the mass ratio of acrylamide (AM) to sodium alginate (SA) of 3:0.6, and then transfer it to a 60 °C constant temperature water bath and continuously stir for 1 h to ensure uniform dispersion of each component. After the mixed solution is cooled to room temperature, inject the crosslinking agent N,N'-methylenebisacrylamide (MBA) at 0.2% of the monomer mass in sequence, and magnetically stir for 1 min to promote molecular pre-crosslinking. Continue to introduce the initiator ammonium persulfate (APS) at 5.0% of the monomer mass, and after short-term stirring, eliminate the residual bubbles by ultrasonic degassing treatment to obtain a homogeneous transparent precursor solution. Use a 1 mL syringe to quantitatively absorb this solution, and carry out thermal-initiated polymerization in a 60 °C water bath environment for 2 h to form a primary crosslinked network. Wash the product with ultrapure water multiple times to completely remove the residual monomers that did not participate in the reaction. Construct a directional pore structure by the ice template method, load the formed hydrogel into a brass mold, and place it in a liquid nitrogen environment for directional solidification treatment to make the ice crystals preferentially grow along the temperature gradient direction. Then transfer it to a freeze dryer and maintain it for 48 h to remove the ice crystal template, and finally obtain a polyacrylamide / sodium alginate-molybdenum disulfide double-network dry gel (PSM) with highly oriented pores. Dissolve lithium chloride with mass gradients (0.09, 0.18, 0.36, 0.54, 0.72, 0.90, 1.08 g) in 10 mL of ultrapure water, then immerse the PSM in each concentration solution for 24 hours, and after directional freezing treatment, finally carry out freeze-drying treatment for 48 hours to successively prepare PSM-0.09L, PSM-0.18L, PSM-0.36L, PSM-0.54L, PSM-0.72L, PSM-0.90L, and PSM-1.08L samples.

[0070] Characterize the directional pore-interconnected porous polyacrylamide / lithium alginate-molybdenum disulfide double-network dry gel (PSML) with a lithium chloride addition amount of 0.9 L prepared in Example 2 of the present invention by SEM, FT-IR, water contact angle, and UV-VIS-NIR.

[0071] The directional channel interconnected porous polyacrylamide / lithium alginate-molybdenum sulfide double network dry gel (PSML) prepared in Example 2 of the present invention was subjected to an indoor moisture absorption and water desorption performance test. The specific process is as follows: the PSML sample prepared in Example 2 was placed in a constant temperature and humidity chamber, and absorbed moisture at a temperature of 25°C and a relative humidity of 90% RH. The moisture absorption amount was 3.68 g / g, and the desorption amount under simulated 1 sun illumination for 1.5 hours reached 2.84 g / g, corresponding to a desorption efficiency increase of 82%.

[0072] In the outdoor experiment of atmospheric water collection driven by solar energy, 23 PSMLs prepared in Example 2 of the present invention were placed in a homemade water collection device for outdoor moisture absorption at night for 12 hours. The next day, natural sunlight was used to desorb the adsorbed water in the sample. The sunlight power density during 1.5 hours of natural sunlight illumination was 0.5 to 0.9 sun, with an average of 0.8 sun. During the illumination period, water mist appeared on the wall of the condensation cover within 10 minutes, and the water adsorbed by the sample was gradually released. After 60 minutes, the surface of the condensation cover of the experimental device was densely covered with fine water droplets. After measurement, the amount of water released from the sample was 1.27 g / g. However, due to objective factors such as residual moisture on the inner wall of the device and heat loss, the actual amount of water collected was 1.04 g / g. It was calculated that the average daily water production of the present invention in the solar drive mode can reach 2.99 L / (m 2 ·d).

[0073] Example 3

[0074] Dissolve 2 mmol of sodium molybdate and 4 mmol of L-cysteine in 30 mL of ultrapure water, then place it in a hydrothermal reactor for hydrothermal reaction. The hydrothermal reaction temperature is 200 °C and the hydrothermal time is 12 h. Then dry it at 80 °C to obtain molybdenum sulfide nanosheets. Disperse 3.0 g of acrylamide monomer and 0.1 g of molybdenum sulfide nanosheets in 30 mL of ultrapure water, and ultrasonic treatment for 20 min to achieve uniform dispersion. Add the corresponding amount of SA powder according to the mass ratio of acrylamide (AM) to sodium alginate (SA) of 3:1, and then transfer it to a 60 °C constant temperature water bath and stir continuously for 1 h to ensure the uniform dispersion of each component. After the mixed solution is cooled to room temperature, inject the crosslinking agent N,N'-methylenebisacrylamide (MBA) at 0.2% of the monomer mass in turn, and magnetic stirring for 1 min to promote molecular pre-crosslinking. Continue to introduce the initiator ammonium persulfate (APS) at 5.0% of the monomer mass, and after short-term stirring, eliminate the residual bubbles by ultrasonic degassing treatment to obtain a homogeneous transparent precursor solution. Use a 1 mL syringe to quantitatively absorb this solution, and carry out thermal-initiated polymerization in a 60 °C water bath environment for 2 h to form a primary crosslinked network. Wash the product with ultrapure water multiple times to thoroughly remove the unreacted monomer residues. Construct a directional pore structure by the ice-templating method. Load the shaped hydrogel into a brass mold and place it in a liquid nitrogen environment for directional solidification treatment to make the ice crystals preferentially grow along the temperature gradient direction. Then transfer it to a freeze dryer and maintain it for 48 h to remove the ice crystal template, and finally obtain a polyacrylamide / lithium alginate-molybdenum sulfide double network dry gel (PSM) with highly oriented pores. Dissolve mass gradients (0.09, 0.18, 0.36, 0.54, 0.72, 0.90, 1.08 g) of LiCl in 10 mL of ultrapure water, then immerse the PSM in each concentration solution for 24 hours, after directional freezing treatment, and finally freeze-dry for 48 hours to obtain PSM-0.09L, PSM-0.18L, PSM-0.36L, PSM-0.54L, PSM-0.72L, PSM-0.90L, PSM-1.08L samples in turn.

[0075] Characterize the directional pore interconnected porous polyacrylamide / lithium alginate-molybdenum sulfide double network dry gel (PSML) with a lithium chloride addition amount of 0.9 L prepared in Example 3 of the present invention by SEM, FT-IR, water contact angle, and UV-VIS-NIR.

[0076] Carry out indoor moisture absorption performance test on the directional pore interconnected porous polyacrylamide / lithium alginate-molybdenum sulfide double network dry gel (PSML) prepared in Example 3 of the present invention. The specific process is as follows: Place the PSML sample prepared in Example 1 in a constant temperature and humidity chamber, and absorb moisture at a temperature of 25 °C and a relative humidity of 80% RH. The moisture absorption amount is 1.45 g / g.

Claims

1. A preparation method of a double-network aerogel with directionally interconnected channels, characterized in that It includes the following steps: Step 1: First, mix acrylamide monomer, molybdenum disulfide nanosheets and sodium alginate powder in a mass ratio of 3:0.1 - 0.3:0.15 - 1, then disperse them in 35 mL of ultrapure water. After ultrasonic treatment, add a crosslinking agent and an initiator, and stir evenly to form a homogeneous transparent precursor solution; Step 2: Inject the precursor solution into a mold, and carry out thermal-initiated polymerization in a water bath environment at 50 - 70 °C for 1 - 3 h to form a primary crosslinked network to obtain a shaped hydrogel. Then load the shaped hydrogel into a brass mold, place it in a liquid nitrogen environment for directional freezing treatment, and then transfer it to a freeze dryer to maintain for 48 h to remove the ice crystal template, and finally obtain a polyacrylamide / sodium alginate-molybdenum disulfide double network dry gel (PSM) with highly oriented pores; Step 3: Dissolve lithium chloride in ultrapure water to obtain a lithium chloride solution. Then immerse the PSM in a lithium chloride solution with a concentration of 0.009 - 0.108 g / mL for 24 hours. After directional freezing treatment, and then carry out freeze-drying treatment for 48 hours to obtain a polyacrylamide / lithium alginate-molybdenum disulfide double network dry gel (PSML).

2. The preparation method of the double-network dry gel with oriented pore channels interconnected according to claim 1, characterized in that: The molybdenum disulfide nanosheets are prepared by dissolving sodium molybdate and L-cysteine in a molar ratio of 2:4 in 30 mL of ultrapure water, then placing them in a hydrothermal reactor for hydrothermal reaction. The hydrothermal reaction temperature is 200 °C, the hydrothermal time is 12 h, and then dried at 80 °C.

3. The preparation method of the double-network dry gel with oriented pore channels interconnected according to claim 1, characterized in that: The crosslinking agent is N,N'-methylenebisacrylamide, and its content is 0.05 - 0.20% of the monomer mass.

4. The preparation method of the double-network dry gel with oriented pore channels interconnected according to claim 1, characterized in that: The initiator is ammonium persulfate, and its content is 5.0% of the monomer mass.

5. The polyacrylamide / lithium alginate-molybdenum disulfide double network dry gel (PSML) obtained by the preparation method according to any one of claims 1 - 4.

6. The application of the polyacrylamide / lithium alginate-molybdenum disulfide double network dry gel (PSML) according to claim 5 in solar-driven air moisture absorption for water production.

Citation Information

Cited By

  • Composite thermosensitive hydrogel as well as preparation method and regeneration method thereof

    CN121949875A